The female directors' effect on a firm's performance: Evidence using US firms - Nafisah Yami; Hashem Alshurafat; Mohamed Shaaban Ibrahim Shaaban (Acta Psychologica)
This paper aims to investigate the impact of female directors on firms' performance, employing two distinct analytical approaches: difference-in-differences and event study. The study employs a difference-in-differences analysis, incorporating a sample of 220 female directors' appointments that are systematically compared with an equivalent set of male directors' appointments using the propensity score approach. Furthermore, an event study technique was employed to assess investor responses to the appointment of female directors versus male directors. The presence of female directors and firm performance were found to be statistically significantly positively correlated through the difference-in-differences analysis. Investors may not respond differently to the appointment of female directors than they do to the appointment of their male counterparts, according to the event study's results, which did not reveal statistical significance on this issue. By applying both difference-in-differences and event study approaches to thoroughly examine the effect of female directors on business performance, this study offers significant insights. The contradictory results highlight the complexity of this relationship and underscore the importance of methodological decisions in understanding how gender diversity impacts business outcomes.